The transformation of the political system in Poland after the breakthrough in 1989 - Shafranska Anna (Borys Grinchenko Kyiv Metropolitan University, 2017)
The transformation of the political system in Poland after the breakthrough in 1989 was expected to change the Polish school. As an effect of the reforms carried out in the late 1980s, the existing hierarchical order, with strongly centralized power and the well-developed system of control and supervision was replaced by the democratic order. It was expected that the results of those transformations would be seen in all spheres of life, including education. Therefore, the changes were meant to affect the existing professional model of teachers, which could contribute to the implementation of many wide changes in their professional sphere. However, not all transformations turned out to be well-aimed and they brought about a lot of new, often worrying, phenomena. The situation of teachers in Poland is largely determined by political activities. Although the political system has changed, the introduced reforms are mostly of political nature. The findings of the research show that a number of facts are regarded as a prerequisite for successful reform in the developed models of change and modernization. However, due to complexity of reforming changes in education, they rarely succeed. Should education be allowed to be spontaneously changed? Should the process of educational change be given to politicians for them to be able to carry out their own experimental educational vision? Of course not. There should be an optimal model to implement change and innovation, being looked for. The only thing is certain: the success of any reform is in the hands of teachers. As long as politicians do not understand that, they will try to implement reforms designed in their offices. Such kind of changes fail, which is shown by the analysis of the ongoing reforms implemented in Poland. Assessing the effects of changes in education, no one looks at those who actually followed them, carrying out the unwanted, unprepared reforms.